PENGARUH FAKTOR BERMUKIM MASYARAKAT TERHADAP POLA PERSEBARAN PERMUKIMAN DI KAWASAN RAWAN BENCANA LONGSOR KABUPATEN MAGETAN - Adryan Aji Saiful Bachry; Ana Hardiana; Rufia Andisetyana Putri (ARSITEKTURA, 2016)
Housing and settlements is fundamental human need to do daily activities for the survival of mankind. The community in determining the location of settlements have basic considerations that affect them in choosing a location for a settlement. The basic consideration is composed of several factors, including accessibility, environment, job opportunities, level of service, in addition to psychological factors, socioeconomic factors and historical cultural factors. Basically the location of settlements or housing are not allowed on the mountain slopes are potentially landslide disaster. Landslide that is threatening the survival of human beings who lived in the area. The danger of a disaster is a natural or artificial phenomena which have the potential to threaten human life, loss of property and damage to the environment. The area of the slopes of Mount Lawu which has a dense contour and topography make settlement patterns that are located in the area most are clumped as well as the distance between one another with their distance. There are several factors that affect the formation of settlement patterns, namely economic, cultural, institutional and customs. The issue of this study is to examine how the influence factors of settlement in the area of  landslide-prone Magetan against  pattern of settlement that is formed in the area. This study discusses the characteristics of the factor pattern of distribution in the community, the establishment of settlements and the influence factors of settlement against the spread pattern of settlement in the area of the landslide-prone Magetan by using multiple linear regression analysis. The community has its own considerations against the selection of the location of the settlement which made slopes be settled and be against the formation of settlement patterns in the Poncol Districts and Plaosan Districts which located on the slopes of Mount Lawu. Of research results obtained in the area of community based factors prone to landslide has no influence on the pattern of the spread of settlements that was formed in the area.